PG75 COVID-19 multidisciplinary and multispecialty adult simulation in the emergency department. (10th November 2020) - Jutla, Sandeep; Knapp, Scott; Fudge, Jake; Davies, Ffion
Abstract : Background: As part of our local Emergency Department (ED) preparations for COVID-19, we designed and delivered a simulated scenario to test our departmental and cross-speciality processes when dealing with a critically unwell patient. Within 48 hours we were able to run a large-scale simulation with other medical and non-medical specialities. We used a high-fidelity mannequin to allow staff to practice invasive clinical procedures in the Emergency Room (ER), and then safely transfer the mannequin to the Intensive Care Unit (ICU) 1 . Feedback from all participants was used to generate a list of immediate actions that could be implemented at short notice. Summary of Work: The simulation took place in the ER involving juniors and seniors from the following staff groups: ED doctors and nurses, Operating Department Practitioners, ICU team, Infection Prevention team, Radiographers, Health Care Assistants, Security, Porters and Ward Clerks. The simulation lasted for one hour (inclusive of transfer to ICU), followed by a debrief with all participants. The scenario was based around a patient presenting in acute respiratory failure after returning from Italy, with suspected COVID-19. Facilitators would observe technical and non-technical skills demonstrated throughout. The scenario was followed by a detailed debrief session where staff were able to reflect on their experiences and suggest improvements. Summary of Results: Technical skills observed: effective and structured A-E primary assessment; early identification of acute respiratory failure (with minimal investigations); appropriate clinical management of suspected COVID-19; safe and timely transfer of patient from the ER to ICU. Non-technical skills observed: team leadership with appropriate role allocation; adequate task prioritisation. Discussion and Conclusions: This simulation was well-received by all participants and served as an educational platform for local specialities to come together and formulate rapid solutions. Evaluation of verbal and written feedback from staff members identified the following key issues specific to the ED: lack of preparation prior to patient arrival; poor communication whilst wearing Aerosol-Generating Procedures (AGP) Personal Protective Equipment (PPE); and unsatisfactory donning/doffing procedures 2 . Recommendations: We generated the following immediate actions: a COVID-19 donning/doffing training hub available to hospital staff members; an ER checklist that would help staff safely prepare for an unwell COVID-19 patient; designate the use of smartphones (used on speakerphone) for communication between staff in the ER, and further work developing non-verbal communications. We also created a teaching package that was shared via social media to help other hospitals with their COVID-19 preparations. References: Gordon, JA, Wilkerson WM, Shaffer DW, Armstrong EG. Practicing' medicine without risk: students' and educators' responses to high-fidelity patient simulation. Acad Med 2001;76(5):469–72. Mookherjee S, Cosgrove EM. ed. ( 2016) Handbook of Clinical Teaching [online] Springer, Cham.